Peran Kepala Madrasah Dalam Manajemen Berbasis Sekolah (Mbs) di MI Al Islamiyah Pulau Kijang Kecamatan Reteh Kabupaten Indragiri Hilir - Nur Baidi; Ahmad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2022)
The problem in this study is the role of the head of the madrasah in school-based management (MBS) in MI Al Islamiyah Island Kijang Reteh Riteh Indragiri Hilir district, whatever obstacles and supportive factors are faced, and what efforts are made by the head of the madrasah in school-based management (MBS) at MI Al Islamiyah Island Kijang Reteh Indragiri Hilir district. The purpose of this research is to know how the roles of the leader of the madrasaah in school-based management (MBs) in MI Al Islamiah Island Kiyang Retteh Indragi Hilir District Based on the analysis of the data, the conclusion is: first, to know what obstacle factors and supporting factors are faced, and second, to find out what efforts have been made by the head of a madrasaha in the management of schools (MBAs) at MII Islamiyah island, Kijanga Rateh Madrasai district, Indrahi Hilir. Second, the inhibitory and supportive factors faced by the head of the madrasah are funds or limited data sources relying only on the funds of the boss, and the staff of experts related to management are all focused on the head. Supportive factors are seeking funds from the government and the public, and there are some teachers continuing their studies in major education management so that it will make it easier to run the matrasah with little value or rely entirely on the head of the school. Thirdly, the efforts made by the head of the madrasah are to socialize the concept of school-based management (MBS) to all the citizens of the madrasah, to analyze the situation of the matrasah and outside the school, to formulate a goal, to choose the measures to solve the problem, and to realize the plans that have been made by making the programs to realize the short-term plan of management-based school (MBS).